Pengaruh Jarak Tanam Dan Dosis Pupuk Kandang Sapi Terhadap Pertumbuhan Dan Hasil Kacang Panjang (Vigna cylindrica L): Pengaruh Jarak Tanam Dan Dosis Pupuk Kandang Sapi Terhadap Pertumbuhan Dan Hasil Kacang Panjang (Vigna cylindrica L) - Khasanah, Hepy; Santosa, Sartono Joko; Sigit Saputro, Avisema (innofarm, 2024)
The research is entitle â€œ The Effect in Planting Distance and Cow Manure Dosage at Growth and Yield of Long Beans Plants (Vigna cylindrica L)â€. The research aims to provide the most effective planting distance and dose at cow manure for the growth and yield of long bean plants. Held in December 2023 â€“ February 2024 in the Tohudan Food Plant and Horticulture Seed Garden, Colomadu. The survey used at Completely Randomized Block Design (RCBD) composed in 2 factor at 3 replications, where Factor 1 : S0 = No treatment, S1= 10 tons per hectare, S2= 20 tons per hectare, and S3= 30 tonsper hectare. Factor 2: J1= 20 cm x 40 cm, J2= 25 cm x 40 cm, and S3= 30 cm x 40 cm. Height of plant, number of leaves, weight of wet stover , weight of dry stover, number of pods, length of pods and weight of pods are observation parameters. Data analysis used (ANOVA) a take in the Least Significant Difference (LSD) test of the 5% levels. According to the study's findings, the parameters of height of plant, number of fruit (pods), and length of fruit (pods) were influenced by treatment for planting space. On average, the plant distance treattment of 30 cm x 40 cm produced the high number of fruit (pods), namely 9.13 pods. The parameter for the number of fruit (pods) is influenced by dose of cow manure used. Cow manure dose to 30 tonnes/ha received the highest number of pods, an average of 9.78 pods. There is interaction among cow manure treatment and planting space (30 tonnes/ha of cow manure by a planting space of 25 cm x 40 cm) giving the high average of 219 cm.